JARGON PERETAS YANG DIBENTUK MELALUI PROSES PERLUASAN MAKNA - Erlan Aditya Ardiansyah; Lia Maulida Indriani; Sugeng Riyanto (Humaniora, 2014)
Hackers are computer experts having competence in both programming and technology information languages. This study aims to examine hacking jargon derived from the standard language. It uses words, phrases, and clauses in the English language as the data, collected from the movie transcription. It applies distributional method and descriptive qualitative technique to analyze the data. The results show that the hacking jargons are standard language which have been shifted in meaning. The meaning shift demonstrates relations between the lexical and additional meanings, i.e. correlated meaning, uncorrelated meaning, and new meaning.